Parâmetros geotécnicos estáticos e dinâmicos de areias quartzosa e carbonatadas - Julião, Nathália Rodrigues (2020)
This dissertation aims to study the capture process of carbon dioxide (2 ) in recycled coarse concrete aggregates by reacting that 2 gas with calcium hydroxide (Ca(OH)2), forming calcium carbonate (CaCO3 ). The recycled aggregates, from the crushing of concretes produced in laboratory, are experienced to accelerated carbonation (2 concentration of 20 ± 2 %) during different exposure times (1, 2, 4, 8, 16 and 24h) within a climatic chamber of temperature (23 ± 2 °C) and relative humidity (60 ± 5 %) controls. The carbon capture are assessed from thermogravimetry analysis based on mass of carbon dioxide normalized by the calcium hydroxide content of each sample. In addition, the performance of the treatment are evaluated by water absorption, relative density and thermogravimetry data before and after exposure. The experimental data show that with just one hour of treatment it is already possible to observe an increase in the capture of carbon dioxide, densification and reduced water absorption capacity of the recycled aggregates and that two hours of exposure to the treatment by accelerated carbonation would be the ideal time for optimization of the results (2 capture of 25%, reduced absorption capacity of 24% and increased grains densification of 3%).